Implementation of the Internet of Things (IoT) in the Teacher Attendance System Using the ESP32-CAM Module and Firebase Database - Romy Permana Sitepu; Hafni; Mudammad Zen; Zulfahmi Syahputra (Bahasa Indonesia, 2026)
A routine activity carried out by students and teachers before the teaching and learning process is attendance. Attendance is one of the important components used as a benchmark for assessing attendance and performance. Attendance activities, especially in schools, tend to still use manual methods. So there are still frequent errors in recapitulation and recording of attendance. One of the microcontroller components that supports attendance activities is the ESP 32 Cam. Therefore, research was conducted to create an effective and easy-to-use attendance system based on the ESP 32 Cam. The ESP 32 Cam has the advantage of being equipped with a camera and wifi so that teachers who will take attendance are required to record facial images. This minimizes the occurrence of fraud in the attendance process. Furthermore, the Firebase Database functions as a storage place for teacher attendance data. Firebase Database is a service that provides a cloud-based data storage application in JSON format. In addition, Firebase Database also has the advantage of real-time data synchronization. After conducting research, the ESP32 Cam is not equipped with a good operating system for managing system files. Therefore, the author tried to conduct research by developing a teacher attendance system with the ESP 32 Cam and Firebase Database. The attendance process begins with the administrator registering or recording a facial image. The attendance process is then carried out by bringing the face close to the ESP 32 Cam camera. The identified facial recording is then sent and stored in the Firebase Database. The results of this study indicate that the attendance system can only be used by teachers who have previously registered and only covers teachers at one school.